The role of a radiopaque peri-rectal hydrogel spacer in aiding accurate daily image-guidance for prostate stereotactic radiotherapy - Icht, Oded; Schlosser, Shir; Weinstock-Sabbah, Miriam; Rephael, Mor; Bragilovski, Dimitri; Moore, Assaf; Shochat, Tzippora; Limon, Dror; Fredman, Elisha (Frontiers in Oncology, 2024)
Precise patient positioning with image guidance (IGRT) is essential for safe prostate radiotherapy. We present the first report of utilizing a CT-visible hydrogel spacer, used to decrease rectal radiation dose, as a surrogate fiducial marker to aid in daily IGRT with cone-beam CT (CBCT) in stereotactic radiotherapy (SABR) for prostate cancer.Prior to CT simulation, patients underwent placement of three intraprostatic gold fiducial markers and radiopaque hydrogel spacer per standard practice. At treatment, after initial setup, a CBCT was acquired and fused to the planning CT based on 3dimensional matching of the spacer. A second alignment was then performed based on the fiducial markers. The six directional shifts (three linear and three rotational) were recorded, and the differences compared.Results: 140 individual fractions across 41 consecutive patients were evaluated.Mean/median differences between hydrogel spacer-based and fiducial-based alignment in linear (vertical, longitudinal, lateral) and rotational (rotation, pitch, roll) shifts were 0.9/0.6mm, 0.8/0.5mm, and 0.6/0.4mm, and 0.38/0, 0.62/0, and 0.35/0 degrees, respectively.No difference was observed in 9.9%, 22.9%, and 22.14% of linear shifts, and 65.7%, 65%, and 66.4% rotational shifts, respectively. Significantly smaller differences were observed in the latter 70 fractions vs. the former, and results were consistent across evaluators.For precise daily IGRT with CBCT for prostate SABR, alignment using a radiopaque hydrogel spacer was highly comparable to intraprostatic fiducial markers. This represents the first report supporting an additional indication of IGRT for a CT-visible hydrogel spacer, to further enhance treatment accuracy and potentially obviate the need for the additional fiducial marker procedure.